The Presentation of Identities Thai Song Ethic through Infographic - ศักดา พรพิมล; จุลกะเศียน ธนพล; เครือรัตน์ บวร; นิ่มเจริญ วรางคณา (Siam Communication Review, 2019)
The aim of research for present and convey the identity of Thai Song ethnic group via graphic information, quality and satisfaction evaluation of graphic describing design and development information. The samples used in this research: 1) Ban Hua Tanon community leader, Don Putsha Sub-District, Don Tum District, Nakhon Pathom Province by Purposive Sampling to study the settlement, economy, society, lifestyle and identity of Thai ethnic Thai Song group. 2) The five design experts to assess the quality of Infographics. 3) Fifty people from Villagers, teachers, students in Baan Hua Tanon Road, Don Putsha Sub-District, Don Tum District, Nakhon Pathom Province. The Purposive sampling is used to evaluate the satisfaction of the media designed and developed. The result of research found that the graphic presentation of the ethnic identity of Thai Song ethnic group was designed and developed with the length of 22.5 minutes with in 10 videos, including the history, dressing, habitat, food, occupation, local wisdom, beliefs, traditions, rituals and folk games. The results of the evaluation of the quality of graphic media described by the experts showed that the overall quality of the media was high (x ̅ = 4.24 SD = 0.67). The Satisfaction level of the media design was rated at the high level (x ̅ = 4.20 SD = 0.46). In conclusion, the graphic design is a good quality. This can be used.